Cell therapy with human IL-10-producing ILC2s limits xenogeneic graft-versus-host disease by inhibiting pathogenic T cell responses - Kyle T. Reid; Sarah J. Colpitts; Jessica A. Mathews; Abel Santos Carreira; Julia M. Murphy; Dorota T. Borovsky; Sinthuja Jegatheeswaran; Wenhui Cui; Tommy Alfaro Moya; Nadia Sachewsky; James An; Yubing Xia; et al. (Cell Reports)
Summary: Interleukin-10 (IL-10)-producing group 2 innate lymphoid cells (ILC210) regulate inflammatory immune responses, yet their therapeutic potential remains largely unexplored. Here, we demonstrate that cell therapy with human ILC210 inhibits pathogenic T cell responses in humanized mouse models of graft-versus-host disease (GVHD), resulting in reduced GVHD severity and improved overall survival without limiting the graft-versus-leukemia effect. ILC210 conferred superior protection from GVHD than IL-10−/low ILC2s, and blocking IL-10 and IL-4 abrogated ILC210 protective effects, indicating that these cytokines are important for the protective effects of ILC210. Notably, ILC210 provided comparable protection from GVHD to regulatory T cells without impairing T cell engraftment, instead decreasing intestinal T cell infiltration and suppressing CD4+ Th1 and CD8+ Tc1 cells. CITE-seq of expanded ILC2s revealed CD49d and CD86 are markers that allow for enrichment of ILC210 from conventional ILC2s and tracking of ILC210 in patient studies. Altogether, these findings demonstrate the potential of ILC210 in cell therapies for GVHD and other immune-mediated diseases.